2008
DOI: 10.1029/2007jg000547
|View full text |Cite
|
Sign up to set email alerts
|

Statistical and process‐based modeling analyses of tree growth response to climate in semi‐arid area of north central China: A case study of Pinus tabulaeformis

Abstract: [1] Statistical modeling techniques and the Vaganov-Shashkin (VS) forward model of tree ring formation were used to investigate tree growth response of Pinus tabulaeformis to climate variations in semi-arid north central China. Both statistical and process-based modeling techniques were shown to be capable of simulating and evaluating climate-tree growth relationships for the study area, but the process-based VS model produced results that were more physically interpretable. Statistical modeling results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 34 publications
2
37
0
1
Order By: Relevance
“…This mainly affects higher sites, such as SRS10, where precipitation is higher and temperatures are lower, compared to other sites. This relationship was also found in the Helan Mountains of north central China, where a process-based model study showed that the percentage of days with growth limitation was related to temperature increases, while that related to soil moisture decreases in the late growing season (Shi et al 2008). Further investigation of the inversion of the relation of tree growth and precipitation in September and October is required.…”
Section: Tree Growth and Climatementioning
confidence: 98%
See 2 more Smart Citations
“…This mainly affects higher sites, such as SRS10, where precipitation is higher and temperatures are lower, compared to other sites. This relationship was also found in the Helan Mountains of north central China, where a process-based model study showed that the percentage of days with growth limitation was related to temperature increases, while that related to soil moisture decreases in the late growing season (Shi et al 2008). Further investigation of the inversion of the relation of tree growth and precipitation in September and October is required.…”
Section: Tree Growth and Climatementioning
confidence: 98%
“…In northern China, dendrochronological studies of Chinese pine indicate that the limiting effect of precipitation extends to July (Liu et al 2005, Li et al 2007. A process-based modeling analysis also showed that precipitation prior to and during the growing season has significant effects on Chinese pine growth in semi-arid areas of north central China (Shi et al 2008). However, water stress only extends to May in this study, reflecting the early arrival of the East Asian Monsoon in the region, which explains why tree growth shows no relation with July and August precipitation.…”
Section: Tree Growth and Climatementioning
confidence: 99%
See 1 more Smart Citation
“…In terms of heat condition, such slopy areas are unsuitable for either cold-resistant tree species such as larch and spruce, or oriental arborvitae with high demands for heat [20]. In terms of soil condition, the slopy areas are not ideal for broad-leaved species such as maple, basswood, and oak whose growth requriements of soil moisture and fertility can not be met [15].…”
Section: Discussionmentioning
confidence: 99%
“…For shrub species, the total biomass of all shrubs in a stand was taken as the stand shrub biomass [14]. Water contents of the main roots, lateral roots, stem, branches, and leaves were determined for a standard shrub species and then used to calculate the dry weights (biomasses) of individual organs [15]. The biomasses of individual organs from the standard shrub species was summed up as its total biomass and then multiplied by the plant number of this shrub species in a specific forest stand to obtain the biomass of this species in the stand [16].…”
Section: Figure 1 Location Of the Study Area In Xiaolong Mountain Gmentioning
confidence: 99%